2019
DOI: 10.3390/ijms20184514
|View full text |Cite
|
Sign up to set email alerts
|

NK Cell Hyporesponsiveness: More Is Not Always Better

Abstract: Natural Killer (NK) cells are a type of cytotoxic lymphocytes that play an important role in the innate immune system. They are of particular interest for their role in elimination of intracellular pathogens, viral infection and tumor cells. As such, numerous strategies are being investigated in order to potentiate their functions. One of these techniques aims at promoting the function of their activating receptors. However, different observations have revealed that providing activation signals could actually … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 152 publications
(222 reference statements)
0
13
0
Order By: Relevance
“…Previous reports have shown that NK cells can become unresponsive on repeated administration of cytokines including IL-15 or sustained activation. 47 IL-15-resistance or antidrug antibodies are serious concerns. In this study, tumor-bearing mice received repeated doses of IL-15 or RLI (four times a week for 2 or 3 weeks) with antitumor activity and NK cell modulation observed.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown that NK cells can become unresponsive on repeated administration of cytokines including IL-15 or sustained activation. 47 IL-15-resistance or antidrug antibodies are serious concerns. In this study, tumor-bearing mice received repeated doses of IL-15 or RLI (four times a week for 2 or 3 weeks) with antitumor activity and NK cell modulation observed.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, this pattern has implications for the use of NK cells in therapeutic settings and affects interpretations of how NK cells control virus infections and regulate autoimmunity. Additionally, NK cells act as a rheostat by removing activated CD4+ and CD8+ T cells in viral infections such as HIV and HCV, thus preventing T cell-mediated autoimmunity ( Lodoen and Lanier, 2005 ; Sun and Lanier, 2008 ; Frutoso and Mortier, 2019 ). Based on this knowledge we will comment on immune modulating treatment options that are being a proper strategy for the current COVID-19 crisis.…”
Section: Immunological Aspects Of Sars-cov2 Features Diagnosis and mentioning
confidence: 99%
“…37 Furthermore, they proposed that these findings should inform IL-15 dosing strategies. Frutoso and Mortier, 17 and Frutoso and coworkers 38 provide excellent reviews of 'NK cell hyporesponsiveness: more is not always better'. They outline circumstances where providing additional IL-15 could actually be counterproductive and could lead to NK-cell hyporesponsiveness.…”
Section: Discussionmentioning
confidence: 99%
“…IL-15, a pleiotropic cytokine that stimulates the differentiation and proliferation of natural killer (NK) and CD8 T cells, is among the cytokines showing promise. [4][5][6][7][8][9][10][11][12][13][14][15][16][17] IL-15 signals through a heterotrimeric receptor including the common gamma chain (γc) shared with IL-2, IL-4, IL-7, IL-9 and IL-21, the beta chain shared with IL-2 and a unique IL-15Rα chain. 4 14 15 IL-15Rα and IL-15 are produced in a coordinated fashion predominantly by activated monocytes and dendritic cells.…”
Section: Introductionmentioning
confidence: 99%